2008
DOI: 10.1007/s10620-008-0501-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T-Cell Function Is Impaired in Celiac Disease

Abstract: Celiac disease (CD) is characterized by intolerance to gluten and high risk of developing autoimmune phenomena. Possible defects in immune tolerance could have a role in the pathogenesis of the disease. As regulatory T-cells (Tregs) are the main population involved in maintaining peripheral tolerance, we investigated the number of these cells in celiac patients as compared with healthy donors. Moreover, we analyzed the suppressive function of CD4+CD25+ T-cells from celiac disease patients and controls on autol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 27 publications
4
44
2
1
Order By: Relevance
“…Taken together, these findings confirmed the deficiency of the D2 isoform in down-regulating the Th17 master transcription factor. Previous studies have reported an increase in the number of T reg cells in CD patients and suggested that functional impairments in their suppressive function may be related to the onset of the disease [29][30][31][32]. The exact mechanisms that cause the altered regulatory activity of T reg cells in CD, however, are not understood fully.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these findings confirmed the deficiency of the D2 isoform in down-regulating the Th17 master transcription factor. Previous studies have reported an increase in the number of T reg cells in CD patients and suggested that functional impairments in their suppressive function may be related to the onset of the disease [29][30][31][32]. The exact mechanisms that cause the altered regulatory activity of T reg cells in CD, however, are not understood fully.…”
Section: Discussionmentioning
confidence: 99%
“…While deficiencies in the population of T reg cells have been associated with other autoimmune diseases such as systemic lupus erythematosus (SLE) [28], CD is characterized by an increased number of FoxP3 1 cells in the lamina propria of the small intestine [29,30]. Several groups have shown that their suppressive function is impaired significantly [31][32][33], but the exact mechanisms behind these deficiencies are not understood fully. In the present study, we show that in CD patients the D2 isoform is overexpressed compared to FL in FoxP3-positive cells homing in the gut mucosa and that the intestinal microenvironment, characterized by high production of proinflammatory cytokines and specific microbial-derived metabolites, may contribute to this disequilibrium.…”
Section: Regulatory T Cells (T Reg ) Represent a Subset Of Cd4mentioning
confidence: 99%
“…Surprisingly, expression of FoxP3 was found to be reduced in patients with NCGS compared to CD, perhaps in the context of a generally reduced activation of adaptive immunity in NCGS relative to CD patients [63]. However, the overall expression of this and other messengers (e.g., TGF-β1, and IL-10) represents a rather controversial aspect of CD autoimmunity, because both downregulation and upregulation of FoxP3 and other T reg -dependent molecules have been reported in patients with CD and related autoimmune conditions (e.g., type 1 diabetes mellitus) [72][73][74][75][76].…”
Section: Non-celiac Gluten Sensitivitymentioning
confidence: 99%
“…22 Support However, another study found evidence for reduced Treg function in CD, 32 and even if Treg cells are increased in CD, they do not seem to prevent CD from being associated with many autoimmune diseases. Co-infection or 'co-disease' may lead to a chronic inflammatory process with a concomitant increased CTLA-4 and PD-1 expression on immune cells, which is associated with decreased Th17 and Th1 responses.…”
Section: Mechanismsmentioning
confidence: 99%